Cold War. The complete series - Isaacs, Jeremy, 1932-; Smith, Martin, 1939-; Branagh, Kenneth; Davis, Carl, 1936-2023; Black, Emma; Brady, Shelagh; Dunlop, Alexander, 1971-; Howlett, Jim; Turner Original Productions; Cable News Network; Warner Home Video (Firm) (Burbank, CA : Distributed by Warner Home Video, 2012)
A sweeping look at nearly five decades of global history, a crystallization of a massive, three-year-long effort helmed by award-winning documentarian Jeremy Isaacs (The World at War). Isaacs's team shot more than 1,000 hours of original footage and gathered archival footage from all over the world to include historically important, and often emotionally stunning, images, many never before seen by an international audience.
Disc 1. Comrades (1917-1945) ; Iron Curtain (1945-1947) ; Marshall Plan (1947-1952) ; Berlin (1948-1949) -- disc 2. Korea (1949-1953) ; Reds (1947-1953) ; After Stalin (1953-1956) ; Sputnik (1949-1961) -- disc 3. The Wall (1958-1963) ; Cuba (1959-1962) ; Vietnam (1954-1968) ; MAD (1960-1972) -- disc 4. Make love, not war (the 1960s) ; Red Spring (the 1960s) ; China (1949-1972) ; Detente (1969-1975) -- disc 5. Good guys, bad guys (1967-1978) ; Backyard (1954-1990) ; Freeze, (1977-1981) ; Soldiers of God (1975-1988) -- disc 6. Spies (1944-1994) ; Star Wars (1980-1988) ; The Wall comes down (1989) ; Conclusions (1989-1991).
DVD, region 1, widescreen presentation; Dolby Digital stereo.
English dialogue; French or Spanish subtitles; English subtitled for the deaf and hard of hearing.
Title from container.
Narrator, Kenneth Branagh.
Music, Carl Davis ; editors, Emma Black, Shelagh Brady, Alexander Dunlop ... [et al.] ; cinematographer, Jim Howlett.
Contains all 24 episodes of the television series that aired on CNN in 1998.
Keywords: Cold War; Video recording for the hearing impaired; Nonfiction television programs; Documentary television programs; Historical television programs; Television mini-series.; Video recordings for the hearing impaired